Non-tariff barriers and the Uruguay Round - Rudolf Adlung (Intereconomics, 1990)
The use of non-tariff barriers to trade, which began to be important in the 1970s, has continued to increase throughout the 1980s. Notwithstanding the difficulties and limitations it faces, the Uruguay Round probably presents the only present opportunity of coming to grips with many existing exemptions to, and distortions of, GATT rules.
Keywords: 330; Gatt